Ultrasensitive Photonic Microsystem Enabling Sub-micrometric Monitoring of Arterial Oscillations for Advanced Cardiovascular Studies - Rodríguez-Rodríguez, Rosalía; Ackermann, Tobias Nils; Plaza, Jose Antonio; Simonsen, Ulf; Matchkov, Vladimir; Llobera, Andreu; Munoz-Berbel, Xavier (Frontiers in Physiology, 2019)
Cardiovascular diseases are the first cause of death globally. Their early diagnosis requires ultrasensitive tools enabling the detection of minor structural and functional alterations in small arteries. Such analyses have been traditionally performed with video imaging-based myographs, which helped to investigate the pathophysiology of the microvessels. Since new vascular questions have emerged, substantial modifications are necessary to improve the performance of imaging and tracking software, reducing the cost and minimizing the microvessel cleaning and manipulation. To address these limitations, we present a photonic microsystem fabricated in polydimethylsiloxane and integrating micro-optical elements and a lightguide-cantilever for sub-micrometric analysis of small arteries (between 125 and 400 µm of basal diameter). This technology enables simultaneous measurement of arterial distension, stiffness, vasomotion and heartbeat and without the need for advanced imaging system. The microsystem has a limit of detection of 2 µm, 5 times lower than video imaging-based myographs, is two times more sensitive than them (0.5 µm/mmHg), reduces variability to half and doubles the linear range reported in these myographs. More importantly, it allows the analysis of intact arteries preserving the integrity and function of surrounding tissues. Assays can be conducted in three configurations according to the surrounding tissue: i) isolated arteries (in vitro) where the surrounding tissue is partially removed, ii) non-isolated arteries (in vivo) with surrounding tissue partially removed and iii) intact arteries in vivo preserving surrounding tissue as well as function and integrity. This technology represents a step forward in the prediction of cardiovascular risk.